Isolation, Characterization, and Molecular Modeling of a Rheumatoid Factor from a Hepatitis C Virus Infected Patient with Sjögren’s Syndrome - Yu-Ching Lee; Keng-Chang Tsai; Sy-Jye Leu; Tuan-Jen Wang; Chia-Yu Liu; Yi-Yuan Yang (The Scientific World Journal)
We have previously isolated several IgG rheumatoid factors (RFs) from patients with both rheumatoid arthritis and idiopathic thrombocytopenia purpura using phage display system. To study IgG RFs in patients with other autoimmune diseases, phage display antibody libraries from a hepatitis C virus infected patient with Sjögren’s syndrome were constructed. After panning, a specific clone RFL11 was isolated for characterization in advance. The binding activity and specificity of RFL11 to IgG Fc fragment were comparable to those of RFs previously isolated. The analysis with existed RF-Fc complex structures indicated the homology model of RFL11 is similar to IgM RF61 complex with high binding affinity of about 6×10-8 M. This effect resulted from longer complementarity-determining region (CDR) combining key somatic mutations. In the RFL11-Fc interfaces, the CDR-H3 loop forms a finger-like structure extending into the bottom of Fc pocket and resulting in strong ion and cation-pi interactions. Moreover, a process of antigen-driven maturation was proven by somatically mutated VH residues on H2 and H3 CDR loops in the interfaces. Taken together, these results suggested that high affinity IgG RFs can be generated in patients with Sjögren’s syndrome and may play an important role in the pathogenesis of this autoimmune disease.